The hydro-ethanolic extract of Acacia seyal (Mimosaceae) stem barks induced death in an ER-negative breast cancer cell line by the intrinsic pathway of apoptosis and inhibited cell migration. (15th September 2018) - Zingue, Stephane; Michel, Thomas; Cisilotto, Julia; Tueche, Alain Brice; Ndinteh, Derek Tantoh; Mello, Leônidas João; Njamen, Dieudonné; Creczynski-Pasa, Tânia Beatriz
Abstract: Background: Despite the significant developments occurring in the treatment of cancer, it still remains the second deadly disease, responsible for 8.2 million deaths every year. Various natural substances have been studied for active molecules of tumor suppression in the past and the tropical flora, by its diversity, continues to provide new antitumor drugs. Acacia seyal is a plant used in Cameroonian traditional system to treat cancer. It exhibited cytotoxic effects towards human breast adenocarcinoma cells. The present work was therefore designed to elucidate the underlying mechanisms by which A. seyal extract induced its cytotoxic effect. Methods: The cell death mechanism (apoptosis or necrosis) and cell cycle analyses were assessed using flow cytometry. The levels of reactive oxygen species (ROS), mitochondrial membrane potential (ΔΨm), caspases activities as well as Bcl-2 and Bcl-xL protein contents were assessed in MDA-MB-231 cells. Afterwards, cell migration/invasion was also assessed. Results: The A. seyal extract induced apoptosis in MDA-MB-231 cells, while it failed to do so in MCF-7 cells. It induced cell cycle arrest in G2/M phase. Further it induced a decrease in ΔΨm, an increase in ROS levels and caspases activities as well as a down regulation in Bcl-2 and Bcl-xL protein contents in MDA-MB-231 cells. Moreover, A. seyal extract exhibited anti-migration, anti-invasion activities in MDA-MB-231 cells. Conclusion: These results demonstrate that A. seyal extract induced its antitumor effects mainly by interference in metastasis related events, by triggering apoptosis through a ROS-mediated mitochondrial pathway. Graphical abstract: